2019
DOI: 10.1007/s10107-019-01363-6
|View full text |Cite
|
Sign up to set email alerts
|

Gradient descent with random initialization: fast global convergence for nonconvex phase retrieval

Abstract: This paper considers the problem of solving systems of quadratic equations, namely, recovering an object of interest x ∈ R n from m quadratic equations / samples yi = (a i x ) 2 , 1 ≤ i ≤ m. This problem, also dubbed as phase retrieval, spans multiple domains including physical sciences and machine learning.We investigate the efficacy of gradient descent (or Wirtinger flow) designed for the nonconvex least squares problem. We prove that under Gaussian designs, gradient descent -when randomly initialized -yield… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 43 publications
5
173
0
Order By: Relevance
“…By construction of the variational form, the resulting distribution will be close to |ψ in but slightly perturbed. Adding small random perturbations helps to break symmetries and can, thus, help to improve the training performance [33][34][35]. To create a randomly chosen distribution, we set |ψ in = |0 ⊗3 and initialize the parameters of the variational form following a uniform distribution on [−π, π].…”
Section: A Simulation Studymentioning
confidence: 99%
“…By construction of the variational form, the resulting distribution will be close to |ψ in but slightly perturbed. Adding small random perturbations helps to break symmetries and can, thus, help to improve the training performance [33][34][35]. To create a randomly chosen distribution, we set |ψ in = |0 ⊗3 and initialize the parameters of the variational form following a uniform distribution on [−π, π].…”
Section: A Simulation Studymentioning
confidence: 99%
“…The log-sigmoid activation function was selected for all the neurons. Several initialization methods for weights and thresholds were tested and results showed that the Gaussian random initialization method [19,20] performed the best. The Levenberg-Marquardt training method [21,22] was used in adjusting the weights and offsets in the backpropagation training process.…”
Section: Methods Developmentmentioning
confidence: 99%
“…[36] reveal that the nonconvex objective (1.5) actually has a benign global geometry: with high probability, it has no bad critical points with m ≥ Ω(n log 3 n) samples 4 . Such a result enables initialization-free nonconvex recovery 5 [42,43].…”
Section: Comparison With Literaturementioning
confidence: 99%